Electrospun nanofibres to mimic natural hierarchical structure of tissues: application in musculoskeletal regeneration. (5th April 2017) - Sankar, Sharanya; Sharma, Chandra S.; Rath, Subha N.; Ramakrishna, Seeram
Abstract: Biomimetic scaffolds mimicking the natural hierarchical structure of tissues have recently attracted the interest of researchers and provide a promising strategy to resemble the nonhomogeneous property of tissues. This review provides an overview of the various hierarchical length scales in the native tissues of the musculoskeletal system. It further focuses on electrospinning as a technique to mimic the tissue structures with specific emphasis on bone. The effect of cellular alignment, infiltration, vascularisation, and differentiation in these nanostructures has also been discussed. An outline of the various additive manufacturing techniques in combination with electrospinning has been elaborated. The review concludes with the challenges and future directions to understand the intricacies of bottom‐up approach to engineer the systems at a macroscale. Copyright © 2016 John Wiley & Sons, Ltd.